The Role of Constitutional Law in Achieving Political Stability and Social Justice in Indonesia - Marjan Miharja; Sulis Setyowati; Suhendar; Achmad Zahruddin (Faculty of Law, Universitas Pekalongan, 2025)
Ahmad, A. (2024). Analysis of the Legal Outputs of State Institutions: The Case of the Constitutional Court of the Republic of Indonesia. Enigma in Law, 1(2), 36–40. https://doi.org/10.61996/law.v1i2.35 Annisa Salsabila, Tria Noviantika, & Ahmad Yani. (2024). Initiating Constitutional Morality: Political Intervention, Ethical Reinforcement, and Constitutional Court Decisions in Indonesia. Constitutional Review, 10(2), 505–537. https://doi.org/10.31078/consrev1028 Anogara, S., Ferdiansyah, M., Esfandiari, F., & . S. (2024). Analysis of the Mechanism for Dismissal of Judges of the Constitutional Court by the House of Representatives of the Republic of Indonesia. KnE Social Sciences. https://doi.org/10.18502/kss.v8i21.14765 Aprilia, H. N., & Fartini, A. (2024). Human Rights Guarantees for People with Mental Disorders in The Indonesian Constitution. Jurnal Mahasiswa Hukum Islam, 1(2), 121–135. https://doi.org/10.37035/jurhis.v1i2.9524 Baik, J. (Sophia), & Sridharan, H. (2024). Civil rights audits as counterpublic strategy: articulating the responsibility and failure to care for marginalized communities in platform governance. Information, Communication & Society, 27(5), 836–855. https://doi.org/10.1080/1369118X.2023.2227685 Daswanto, D. (2024). Legal Policy of Pretrial Arrangements in Criminal Procedure Law in Indonesia by the Constitutional Court. Interdiciplinary Journal and Hummanity (INJURITY), 3(11), 755–767. https://doi.org/10.58631/injurity.v3i11.1309 Dollu, D. Y., & Fatima, R. N. (2024). Problem from mk powerful number 90/Puu- Xii/2023 related to article 169 letter Q number 7 Year 2017 about general election (Election Law). Journal of Multidisciplinary Academic and Practice Studies, 2(3), 317–323. https://doi.org/10.35912/jomaps.v2i3.2245 Fadrial, R., Sujianto, S., Tua Ricky Freddy Simanjuntak, H., Wirman, W., & Setiawan Wibowo, W. (2024). Fostering Trust Through Bytes: Unravelling the Impact of E-Government on Public Trust in Indonesian Local Government. Interdisciplinary Journal of Information, Knowledge, and Management, 19, 015. https://doi.org/10.28945/5317 Farid, A. M. F., & Nanik, N. P. (2023). Legal Reasoning of the Constitutional Court Verdict Number 25/PUU-XX/2022 on the State Capital Law According to Social Justice Value. Jurnal Jurisprudence, 12(2), 217–232. https://doi.org/10.23917/jurisprudence.v12i2.1285 Hidayat, A. (2024). The Impact of Globalization on the Dynamics of the Constitutional Law System in Indonesia: An Analytical Review. Pena Justisia: Media Komunikasi Dan Kajian Hukum, 23(3), 2009–2020. https://doi.org/10.31941/pj.v23i3.4332 Hidayat, R. N., & Novrizal, M.-. (2024). Strengthening the Constitutional Court’s Authority to Adjudicate on Disputes Regarding the Result of Regional Head Election In Indonesia: an Urgency to Clarify the Constitutional Framework. Pena Justisia: Media Komunikasi Dan Kajian Hukum, 23(1), 373. https://doi.org/10.31941/pj.v23i1.4022 Ihza Ibrahim. (2024). ANALISIS LEGAL STANDING PEMOHON DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90/PUU-XXI/2023. Khuluqiyya: Jurnal Kajian Hukum Dan Studi Islam. https://doi.org/10.56593/khuluqiyya.v6i2.135 Lutfi, F., Pramono, S. E., & Masrukhi, M. (2024). The Role of BPIP in Indonesia’s Legal Reform: Navigating Social Transformation and Ideology Education Challenges. Journal of Law and Legal Reform, 5(4). https://doi.org/10.15294/jllr.v5i4.18921 Moh. Thohir, & Didik Sukriono. (2024). IMPLEMENTATION AUTHORITY OF THE CONSTITUTIONAL COURT IN THE INDONESIAN CONSTITUTIONAL LAW SYSTEM. Awang Long Law Review, 6(2). https://doi.org/10.56301/awl.v6i2.1112 Mukherjee, A. (2024). Efficacy of Legal Aid: Bridging the Justice Gap. Galore International Journal of Applied Sciences and Humanities, 8(3), 29–41. https://doi.org/10.52403/gijash.20240304 Rahaditya, R., Rachmat, L. I., Sari, R. A. D. P., & Nugroho, Y. A. (2024). Transformation of the Indonesian Constitutional System Through Amendments to the 1945 Constitution. QISTINA: Jurnal Multidisiplin Indonesia, 3(1), 740–748. https://doi.org/10.57235/qistina.v3i1.2412 Reza, M. F., Zahara, F., & Khalid, K. (2024). Judicial Considerations in Granting and Rejecting Child Madiyah Support Claims from a Progressive Legal Theory Perspective (A Normative Juridical Study of Decision No. 1172/Pdt.G/2018/PA.Smd. and Decision No. 41/Pdt.G/2014/PA Tkl.). Journal of Law, Politic and Humanities, 4(6), 2314–2325. https://doi.org/10.38035/jlph.v4i6.733 Rudy, E., & Adang Supriyadi, A. (2025). Security Policy Transformation to Accelerate the Achievement of the Sustainable Development Goals (SDGs) in Papua. https://doi.org/10.20944/preprints202501.1975.v1 Sapsudin, A., & Qohar, H. A. (2024). Constitutional Law Reform to Realize Inclusive Higher Education for Persons with Disabilities. JURNAL AKTA, 11(4), 1320. https://doi.org/10.30659/akta.v11i4.40699 Siregar, D. P., & Wisnaeni, F. (2024). Political Legal Dissenting Opinion Ruling in the Dispute Cases on the Results of the 2024 Presidential General Election by Constitutional Judges. International Journal of Social Science and Human Research, 7(07). https://doi.org/10.47191/ijsshr/v7-i07-94 Sudiartha, I. B. P., Sihotang, E., & Suandika, I. N. (2024). Kewenangan Mahkamah Konstitusi Dalam Memutus Perselisihan Hasil Pemilu Sebagai Bentuk Judicialization of Politic. Ethics and Law Journal: Business and Notary, 2(2), 166–181. https://doi.org/10.61292/eljbn.191 Syahrain, A., Sugitanata, A., & Aminah, S. (2024). Political Moderation as a New Foundation in Indonesia: An Analysis of Deliberative Democracy Theory and Maqashid Shariah. An-Nida’, 48(2), 123. https://doi.org/10.24014/an-nida.v48i2.28985 Wadipalapa, R., & Tyson, A. (2025). Cross-Party Presidential Dynasticism in Indonesia: Evidence from the 2024 Presidential Elections. Pacific Affairs. https://doi.org/10.5509/2025981-art4 Zara, M. Y. (2021). Indonesian Mockery of the Dutch during the Indonesian Struggle to Maintain Independence (1945-1948). BMGN - Low Countries Historical Review, 136(3), 31–60. https://doi.org/10.51769/bmgn-lchr.6885 Zhen, R. (2024). Balancing Governance and Rights: The Interplay Between Constitutional and Administrative Law. Communications in Humanities Research, 32(1), 196–201. https://doi.org/10.542 54/2753-7064/32/20240070